De Hongaren en het onderwijs aan de Friese universiteit te Franeker - Postma, Ferenc (Acta Neerlandica, 2015)
After the Fall and Destruction of Heidelberg (September 6, 1622) Protestant Students from Hungary and Transylvania came in a mass to the Northern Netherlands, in order to continue their studies there at the Dutch Universities, especially in Philosophy, Theology and Medicine. So the first group of Hungarian Students arrived at Franeker (in Frisia) at the end of August, 1623. Until the year 1811, as the University was closed, we can detect more than 1.200 Hungarian names in the Franeker Album Studiosorum, a much larger number of Hungarians than everywhere else in the Netherlands. In this article we offer some reasons, why the University at Franeker was such a favourite place for the Hungarians. Moreover we stress the direct interaction between these Students and the Franeker Professors, concerning the topics treated in their Lectures, f.e. in the case of Professor Nicolaus Vedelius (1596-1642), Professor Nicolaus Arnoldus (1618-1680) and especially Professor Johannes Cloppenburg (1592- 1652). Besides the Professors took often care for the publication of many books written by the Hungarians, to be used in the Schools and Colleges in Hungary and Transylvania itself, as f.e. Professor Johannes Coccejus (1603-1669) did, even by publishing his own Hebrew Psalter (1646) for that purpose. In this way the fame and the glory of the University at Franeker became a reality in the Hungarian Protestant World, even after the University was closed. Generally spoken the Hungarian Students took active part in the Lectures and the Disputations. Two of them got a Degree in Philosophy, five became a Doctor of Theology, and at least ten Students got their Degree in Medicine. The general academic circumstances resp. conditions under which the Hungarians had to study at Franeker, it means the rules for ‘Lectio’ and ‘Disputatio’, we sketch out in the final part of this article.